Model checking in isomorphic module systems - Wang, Weilin (2020)
With a growing number of interacting modules in today's complex systems, finding an effective tool for detecting design errors has become increasingly challenging. We present procedures for analyzing blocking or deadlock in systems consisting of isomorphic modules instantiated from a template. These procedures identify all possible blocking or deadlock sources and directly compute the maximum number of isomorphic modules under which the system is guaranteed to be nonblocking or deadlock-free.